Professors of Church law at Russian universities and theological academies in 1906‒1917 - Olga Iliukhina (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2023)
The article examines the scientific potential of higher schools of the Russian Empire, universities and theological academies, in the field of ecclesiastical law during the active discussion of church reforms in 1906-1917. The author comes to the conclusion that at the beginning of the XX century it is necessary to talk about three developed scientific schools of ecclesiastical law: the St. Petersburg University school of M.I. Gorchakov, associated with it the Moscow University school of N.S. Suvorov and the Kazan School of I.S. Berdnikov. At the same time, only the latter one can be described as having preserved a close connection between the academy and the university. Universities were aimed at replacing the staff of the departments of ecclesiastical law with their graduates. In St. Petersburg and Moscow, it was possible to do this at the beginning of the XX century: V.N. Beneshevich and P.V. Gidulyanov, university graduates, became professors of the Department of Ecclesiastical Law. And the statistics of doctoral dissertations reveal the special role of Moscow University in the training of secular specialists in ecclesiastical law and shows that university scientific schools should be recognized as dominant in science. Strict administrative control and frequent changes of professorial staff at the departments of ecclesiastical law in the St. Petersburg and Moscow Theological Academies in the examined period obviously hindered the development of their own stable scientific traditions. Some stagnation is also noticeable in the Kiev Academy, where M.I. Mishchenko, the Master of Theology, was permanently at the similar department during this period. The inclusion of ecclesiastical law in the list of legal sciences has significantly expanded the scope of research: in addition to the actual study of history or the interpretation of the canons, church-state relations, problems of freedom of conscience, the relationship of the church court and state jurisdiction, as well as civil and family law began to be studied. Scientific achievements turned out to be relevant in the preparation of church reform in pre-Council forums, where university professors were invited mainly.